CLASSIFICATION OF MRI (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The work considers the design of the MRI tomography apparatus and the general algorithm for conducting MRI studies. It is shown that MRI studies take 30-60 minutes, where it is also possible to use systems for monitoring vital functions and lung ventilation. Depending on the structure of the medical organization, the conclusion and images are given to the patient or transferred to the attending physician.